Sleep in Genetically Confirmed Pantothenate Kinase-Associated Neurodegeneration: A Video-Polysomnographic Study - Maria Livia Fantini; Giovanni Cossu; Andrea Molari; Monia Cabinio; Ozlem Uyanik; Roberto Cilia; Maurizio Melis; Angelo Antonini; Luigi Ferini-Strambi (Parkinson's Disease)
Pantothenate kinase-associated neurodegeneration (PKAN) is a familial or sporadic disease characterized by extrapyramidal and corticospinal signs with dementia. Patients show iron accumulation in the basal ganglia, with neuronal loss and gliosis. A mutation of pantothenate kinase (PANK2) gene localized on chromosome 20p13 has been described in familiar forms, as well as in sporadic patients. We sought to assess sleep characteristics, including muscle activity during REM sleep, in three patients with PANK2 gene mutation-confirmed diagnosis of PKAN. Sleep architecture was altered in all patients with reduced total time of sleep in two and lack of SWS in one. No significant apnea/hypopnea were detected, and mild PLMS were observed in one patient (PLMS index:10.7/h). In contrast with other neurodegenerative diseases, no REM sleep abnormalities, especially REM sleep behavior disorder, were observed in PKAN patients, and percentage of both REM sleep atonia and phasic EMG activity were within normal ranges. Sleep studies may phenotypically differentiate PKAN from other neurodegenerative disorders.